Coupling of functionality to trafficking of KCNQ2/3 potassium channels at the axon initial segment - Daisuke Yoshioka; Yasushi Okamura (Proceedings of the National Academy of Sciences, 2026)
KCNQ2/3, a major voltage-gated potassium channel at the axon initial segment (AIS), plays a crucial role in controlling neuronal excitability. While the functionality of KCNQ2/3 is regulated by conformational changes from voltage sensing, the AIS localization of KCNQ2/3 is regulated by ankyrinG (ankG). However, the potential coupling between the mechanisms governing channel functionality and trafficking remains unresolved. Here, we combine genetic engineering of channel functionality with advanced imaging techniques of channel trafficking to uncover a coupling of KCNQ2/3 functionality to trafficking. Single-molecule imaging reveals that reduced KCNQ3 functionality alters the entire trafficking pathway, including exo/endocytosis and lateral diffusion, reducing AIS localization of KCNQ2/3. Furthermore, we develop a live-cell assay to quantify the interactions between full-length KCNQ3 and ankG, demonstrating that the active conformation of KCNQ3 is essential for the stable ankG binding. Our findings establish a mechanistic basis for the integration of KCNQ2/3 gating and trafficking in regulating neuronal excitability.